Effectiveness of Environmental Education Programs for College Students in Enhancing Sustainability Education for SDG’s 2030 : A Systematic Literature Review - Saifana Iluj’ Dhia Hakiki; Diki Anggi Saputra (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
The purpose of this study is to identify the challenges and barriers faced especially in the environment and student education and evaluate the effectiveness of environmental education programs for students in improving sustainability education based on the Sustainable Development Goals (SDGs) 2030 analyzed by a systematic literature review. This study used a systematic literature review research approach guided by the Preferred Reposrting Items for Systematic Review and Meta-Analysis (PRISMA). This research concludes that environmental education in higher education integrated with the 2030 Sustainable Development Goals (SDGs) plays an important role in building students' understanding, skills, and critical awareness of complex global environmental issues. This education programme aims to improve students' knowledge, critical thinking skills, and innovative solutions to environmental challenges.